Circles of sustainability: an activity for visualizing synergies and trade-offs in a systems thinking environment - Meghna Dilip; Margaret E. Kerr (Green Chemistry Letters and Reviews)
In 2015, the United Nations created a framework comprising 17 aspirational goals known as the Sustainable Development Goals (SDGs), with a view toward peace and prosperity by 2030. Green Chemistry (GC) has always been recognized as a pathway to sustainability. However, the best solutions cannot be found if we look at each of these separately, but rather it is important to apply a systems thinking approach and recognize the interconnected nature of the systems being studied. In this paper, we present activities that allow learners to visualize synergies and trade-offs with the SDGs when applying a systems thinking approach compared with a narrower perspective. We applied the approach to an industrial example (Nike) and to concerning chemicals such as bisphenols and per-and polyfluoroalkyl substances (PFAS or ‘forever chemicals’). We believe this approach can be modified and used widely for various chemical processes in an educational context.